The Wikileaks fallout: Strategic implications for the U.S.-ASEAN relations - Heydarian, Richard Javad (Animo Repository, 2014)
The late-2010 decision of the anti-secrecy group Wikileaks to release a quarter-million diplomatic cables in coordination with the world's leading news agencies, namely The New York Times, The Guardian, Le Monde, El Pai, Der Spiegel, revealed the tremendous gap between the United states' (U.S.) official rhetoric and high-minded values, on one hand, and the realpolitik behind its day-to-day exercise of foreign policy across the world, on the other. Standing among a privileged group of actors to directly oversee the release of "the largest set of confidential documents" in the public domain, Britain's leading daily The Guardian went so far as forecasting a "global diplomatic crisis", primarily between the U.S. and its allies, as a result of the massive diplomatic revelations. Leading U.S.' allies such as Saudi Arabia were unwavering in their criticisms, with Prince Turki bin Faisal, the former intelligence chief and ambassador of the Kingdom to Washington, warning "America's credibility and honesty are the victim of these leaks," which could, he argued, encourage officials and important foreign contacts to "no longer speak to American diplomats frankly. In short, the Wikileaks disclosures could undermine intelligence-sharing and diplomatic rapport among allied nations -benefiting the U.S.' strategic rivals such as China, Russia, and Iran, which have sought to, in varying forms, drive a wedge between Washington and its partners. Responding to the stern warnings from allies and recognizing the huge strategic implications of the diplomatic leaks, Secretary Clinton was forced to engage in a global "apology tour", constantly trying to reassure allies and ameliorate their grievances. For instance, during her high-profile trip to the Middle East, few months into the massive diplomatic disclosure, she memorably lamented, "I think I will be answering concerns about Wikileaks until the end of my life, not just the end of my tenure as secretary of state. No wonder, the subsequent late-2011 release of confidential cables on Southeast Asia, among the largest of its kind, held the promise of even greater strategic setback for Washington.